Nine anthropometric indices predict hepatic steatosis and assess liver health in adolescents: a population-based study - Chen, Ruanchang; Zhou, Fangzheng; Zhang, Jiayao; Tong, Huanjun; Lu, Baochun (Frontiers in Pediatrics, 2025)
PurposeThe increasing prevalence of obesity among adolescents has resulted in an increase in the incidence of hepatic steatosis; however, the relationship between anthropometric measurements and this condition in youth remains underexplored.AimsTo evaluate the effectiveness of nine anthropometric indicators in predicting the risk of hepatic steatosis in adolescents.MethodsWe assessed several anthropometric indicators, including the abdominal volume index (AVI), body mass index, body roundness index, body adiposity index, conicity index, waist-hip ratio, waist-to-height ratio, and weight-adjusted waist index. Statistical methods such as multivariate logistic regression, smooth curve fitting, and subgroup analysis were employed. Discriminative accuracy was determined using receiver operating characteristic curve analysis, and a tool based on the optimal Youden index was developed.ResultsAll nine indices were significantly correlated with hepatic steatosis in adolescents. AVI demonstrated the strongest predictive ability, with an area under the curve of 0.8454 (95% confidence interval: 0.8221–0.8687, best threshold: 14.9992). Variations in predictive accuracy were observed across racial and ethnic subgroups, highlighting the importance of demographic factors.ConclusionAll nine anthropometric indices are associated with hepatic steatosis, with AVI emerging as the most effective tool for assessing liver health in adolescents.